Percutaneous access versus surgical cut down for TAVR: Where do we go from here?. Issue 7 (12th June 2018) - Ates, Ismail; Cilingiroglu, Mehmet
Key Points: Transcatheter aortic valve replacement is now the standard of care for severe symptomatic aortic stenosis patients who are at high‐surgical risk. Percutaneous approach without a surgical cut down has been increasingly adapted by some centers in USA. Percutaneous approach seems to be associated with shorter hospital stay, similar short and late vascular complications, less disabling stroke, similar mortality as well as significantly less hospital cost. However, this technique also requires operators to be able to manage any vascular complications using advanced endovascular interventions to achieve complete hemostasis.